2015
DOI: 10.1039/c5an01238d
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule array (Simoa) assay with optimal antibody pairs for cytokine detection in human serum samples

Abstract: Concentrations of cytokines in bodily fluids reflect the physiological or pathological state of the patient and can be used for prognosis, disease diagnosis or for monitoring therapeutic efficacy. However, in the bodily fluids of healthy or sub-healthy individuals, many cytokines are present at concentrations that are near or below the detection limits of current methods. Here we selected antibody pairs to be employed in the single molecule array (Simoa) assay for ten cytokines including GM-CSF, TNF-α, IFN-γ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 16 publications
2
60
0
1
Order By: Relevance
“…This analysis, however, has thus far failed due to the low serum detectability of IL-1β. Recent developments of highly sensitive assays, such as the single molecule array (SIMOA®), have resulted in lower detection limits and the ability to accurately quantify IL-1β in the periphery [119,120]. Similarly, the detection of NLRP3-related molecules such as ASC has been made possible due to assays available on the Ella Simple Plex System (ProteinSimple) [103,104].…”
Section: Novel Biomarkers Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…This analysis, however, has thus far failed due to the low serum detectability of IL-1β. Recent developments of highly sensitive assays, such as the single molecule array (SIMOA®), have resulted in lower detection limits and the ability to accurately quantify IL-1β in the periphery [119,120]. Similarly, the detection of NLRP3-related molecules such as ASC has been made possible due to assays available on the Ella Simple Plex System (ProteinSimple) [103,104].…”
Section: Novel Biomarkers Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…Beads are then loaded into a microwell array consisting of 50,000 wells (46 fL wells, each can accommodate only one bead) and sealed in the presence of fluorogenic substrate. Due to extremely small reaction volume, the concentration of fluorescent product easily reaches a detectable range even if only one enzyme molecule is present in the well [ 154 ]. Very low analyte concentrations, i.e., zero or one antigen on each bead, can be directly determined from number of fluorescent wells and total number of beads in the array by digital readout (0 or 1 signal).…”
Section: Cytokine Detection Techniquesmentioning
confidence: 99%
“…This is achieved by using antibodymodified magnetic beads that capture the analyte in solution, followed by binding of asecondary antibody with biotin labels to which streptavidin-b-galactosidase conjugate is attached. TheW alt research group has demonstrated the power of this technique for awide range of assays such as the cancer biomarker prostate-specific antigen, [43] the toxin ricin, [44] cytokines, [45] dengue fever, [46] and bacterial genomic DNA. We refer to this assay format as wide-field sampling/near-field detection measurements.T he detection limits achieved are exquisite:f or biotin-streptavidin it was 350 zm, which is equivalent to 10-20 enzyme labels in a100 mL sample.…”
Section: Wide-field Sampling/near-field Detectionmentioning
confidence: 99%